Review: Natural products from Genus Selaginella (Selaginellaceae) - AHMAD DWI SETYAWAN (Smujo International, 2011)
Abstract. Setyawan AD. 2011. Natural products from Genus Selaginella (Selaginellaceae). Nusantara Bioscience 3: 44-58. Selaginella is a potent medicinal-stuff, which contains diverse of natural products such as alkaloid, phenolic (flavonoid), and terpenoid. This species is traditionally used to cure several diseases, especially for wound, after childbirth, and menstrual disorder. Biflavonoid, a dimeric form of flavonoids, is the most valuable natural products of Selaginella, which constituted at least 13 compounds, namely amentoflavone, 2',8''-biapigenin, delicaflavone, ginkgetin, heveaflavone, hinokiflavone, isocryptomerin, kayaflavone, ochnaflavone, podocarpusflavone A, robustaflavone, sumaflavone, and taiwaniaflavone. Ecologically, plants use biflavonoid to response environmental condition such as defense against pests, diseases, herbivory, and competitions; while human medically use biflavonoid especially for antioxidant, anti-inflammatory, and anti-carcinogenic. Selaginella also contains valuable disaccharide, namely trehalose that has long been known for protecting from desiccation and allows surviving severe environmental stress. The compound has very prospected as molecular stabilizer in the industries based bioresources.